1983
DOI: 10.1093/infdis/147.3.372
|View full text |Cite
|
Sign up to set email alerts
|

Coccidioidomycosis: Factors Affecting the Host-Parasite Interaction

Abstract: The inhaled arthroconidia of Coccidioides immitis mature to form large (30-80 micron) endosporulating spherules. Each spherule releases hundreds of endospores, taxing immunologic reserves. Polymorphonuclear neutrophils (PMNs) are prominent in the lesions of coccidioidomycosis, but their effectiveness is questionable. Arthroconidia possess an antiphagocytic surface derived from the original hyphal outer wall layer. Only 20%-30% of arthroconidia or endospores that are ingested by PMNs are killed. PMNs can digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
96
0
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 31 publications
3
96
0
2
Order By: Relevance
“…In spite of this intense phagocytic response to endosporulation, rarely are the endospores observed within the host cells. Earlier in vitro studies of host phagocyte interaction with Coccidioides have indicated that macrophages and neutrophils are only able to partially inhibit growth of the pathogen; they are unable to kill the organism (2,16,19). We speculated that opsonization of SOWgp-coated endospores produced by the ⌬mep1 mutant strain would result in increased phagocytosis and clearance of the pathogen from infected host tissue.…”
Section: Discussionmentioning
confidence: 98%
“…In spite of this intense phagocytic response to endosporulation, rarely are the endospores observed within the host cells. Earlier in vitro studies of host phagocyte interaction with Coccidioides have indicated that macrophages and neutrophils are only able to partially inhibit growth of the pathogen; they are unable to kill the organism (2,16,19). We speculated that opsonization of SOWgp-coated endospores produced by the ⌬mep1 mutant strain would result in increased phagocytosis and clearance of the pathogen from infected host tissue.…”
Section: Discussionmentioning
confidence: 98%
“…One exception to this observation is in women during pregnancy, where the risk of severe, symptomatic coccidioidomycosis is high and increases the later during pregnancy that infection occurs (122). While it has been presumed that suppression of cellular immunity associated with pregnancy is the major cause for this increased risk, Drutz and coworkers have suggested that hormonal changes that occur during gestation may increase the growth of the fungus and lead to more severe clinical illness (123,124).…”
Section: Characteristics Associated With Symptomatic Coccidioidomycosmentioning
confidence: 99%
“…However, the precise mechanisms whereby macrophages interact with spherules and endospores are not completely understood. In vitro studies suggest that spherules may escape phagocytosis by macrophages (8). Adaptive immunity to Coccidioides has been extensively studied, and it involves primarily CD4 ϩ T lymphocytes.…”
mentioning
confidence: 99%